Experimental determination of the optimal parameters of operation in the process of electrolixiviation and sequential electrodeposition of gold in acid solutions of thiourea from concentrated sulphides - Torres de la Cruz, R. W. (2012)
The research in the laboratory was made operating variables (reactant concentration, pH and oxidation potential) of pyrite leaching gold from river Tablachaca (Ancash Peru) with thiourea (TU) followed by electro-deposition of gold. The experimental study was conducted in three stages: Oxidation of thiourea leaching of gold and gold electroplating. As an alternative to chemical agents, TU oxidation via electrolysis was conducted to obtain formamidine disulphide (FDS), which serves as an oxidizer in the dissolution of gold. The optimum degree of conversion of formamidine disulfide thiourea in 2.5 h was obtained by applying a FEM of 4.5 V with a pH of 1.5. The anodic and cathodic compartments of the electrochemical reactor were separated by an anion membrane with the purpose of eliminating undesired reactions at the cathode. Prior to the leaching step, the mineral was washed with sulfuric acid to remove the acid consuming agents and thereby maintain a constant pH throughout of the leach. During the leaching of gold, we studied the dissolution rates as a function of the concentrations of TU, SDS and pH. Finally, a test was performed on prolonged leaching using the optimum operating parameters obtained in the previous tests. The electro-deposition test was carried out using the technique of electrodialysis in a three- compartment cell. The low consumption of thiourea (1.76 kg / MT mineral) proves to be a viable alternative economically.